Caffeine Enhances the Balance System and Postural Balance in Short Time in Healthy Individuals - Bünyamin Çıldır; Büşra Altın; Songül Aksoy (Turkish Archives of Otorhinolaryngology, 2021)

(untitled)
Objective:This study aimed to explore the effects of caffeine on balance function by determining the extent to which caffeine consumption affects postural sway and balance control in healthy individuals.Methods:Thirty healthy participants aged 20–35 years without any vestibular disorder were enrolled in this study. The participants were randomly divided into two groups, and those in Group 1 were given two cups of regular coffee (300–350 mg) while those in Group 2 were given two cups of decaffeinated coffee. The sensory organization test, the head shake sensory organization test, the limits of stability test, and the adaptation test were performed on all participants before and after coffee intake using computerized dynamic posturography.Results:The sensory organization test composite scores (p=0.001) and the head shake condition 5 (C5) equilibrium scores (p=0.001) of the participants in Group 1 showed a statistically significant increase after coffee intake while the composite scores (p=0.001) and the head shake condition (C5) equilibrium scores (p=0.001) of those in Group 2 showed a statistically significant decrease. There was a statistically significant difference between the two groups in the equilibrium scores in the pitch plane (p=0.001), the yaw plane (p=0.001), and the roll plane (p=0.001) of C5 after coffee intake.Conclusion:Consumption of an appropriate dose of caffeine may enhance body position, postural stability, and voluntary motor control ability. The combined use of the sensory organization test, the head shake sensory organization test, the adaptation test, and the limits of stability test in evaluating the balance mechanism in individuals with normal vestibular findings provides detailed information about postural sway.